Menakar Tafsir Sufistik - M Noor Harisudin (Justicia Islamica, 2007)
This study aims to analyze the Sufi interpretation approach in understanding the Qur'an and its implications for Islamic discourse. This study explores the main characteristics of Sufi interpretation, its method of interpretation, and its relevance in the context of Islamic spirituality. The research method used is library research with a descriptive-analytical approach. The main sources of this research include classical and modern works of Sufi interpretation, as well as related academic studies. The results of the study show that Sufi interpretation emphasizes the inner (esoteric) meaning of the Qur'an through a symbolic approach and mystical experience. This approach provides spiritual depth for seekers of meaning, but also faces criticism regarding subjectivity and methodological limitations. This study emphasizes that Sufi interpretation remains relevant in enriching the understanding of Islam, especially in the aspects of Sufism and spiritual ethics.